Ajaran Islam dalam Praktik Kerjasama Ekonomi Masyarakat Banjar - Nazhifah, Ainun; Muyassar, Muhammad Hafidz; Ananda, Rizqa; Munawarah, Munawarah; Wahidah, Wahidah; Rahmaniah, Amelia; Hanafiah, M. (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
This study examines Islamic teachings in economic cooperation practices among the Banjar community in Banjarmasin using a library research method. The discussion begins with an exploration of the historical process of Islamization in Banjarmasin, which indicates that Islam has become deeply embedded in Banjar culture since the sixteenth century through trade networks and the da’wah of local Islamic scholars. Islamic teachings subsequently shaped the economic behavior of the Banjar community, particularly through the application of muamalah principles such as honesty, justice, trustworthiness, and mutual consent in economic transactions. Furthermore, economic cooperation among the Banjar people is reflected in various practices, including trade partnerships, trust-based transactions, and customary economic relations that align with Islamic norms. The integration of Islamic values within these cooperative practices demonstrates a harmony between Banjar customary law (urf) and Islamic economic principles, emphasizing not only material profit but also ethical conduct and social welfare. This study concludes that Islamic teachings play a significant role in shaping economic cooperation practices among the Banjar community in Banjarmasin, illustrating a contextual model of Islamic economic values integrated with local culture.